Analysis of Runoff Curve Number Distribution into Surface Runoff of Lesti Watershed - Priambodo, Didit; Suhartanto, Ery; Sumiadi, Sumiadi (Fakultas Teknik UB, 2021)
Lesti watershed is a sub basin of Brantas River located in Malang Regency, which is the main source of inflow and sediment loads for the Sengguruh Dam. Human activities change the type of land cover by deforestation for the expansion of agricultural and residential areas. It makes a rapid increasing of runoff and discharges that were potentially carrying sediment into Lesti River. To measure surface runoff in a watershed can be held by modeling rather than directly in the field, it is cheaper and more effective with accurate results. This study is based on Soil Conservation Service (SCS) formula to illustrate surface runoff level by knowing curve number distribution. Using models based on land use changes in 2010, 2012 and 2017, generated by AV SWAT software, shows that increasing CN value each year affects the surface runoff, so there is a relationship between land use and runoff. The average CN value in 2010 is 63.644, 2012 is 63.942, 2017 is 65.49, while the average surface runoff in 2010 is 800.28, 2012 is 823.26, 2017 is 828.009. Conservation treatment on the area with a high CN value can reduce the surface runoff. It shows that watershed performance is getting better.